FINANCIAL RATIO WHICH AFFECTS THE COMPANY'S FINANCIAL PERFORMANCE - Kurnia, Kurnia; David, Rooney (SYNTIFIC, 2024)
Background. The company's financial health is very necessary to maintain its existence company. BUMN Ministerial Decree No: Kep-100/MBU/2002 to assess the level of health of BUMN is also needed to assess the performance of BUMN subsidiaries. Research Purpose. This research aimed to determine the level of financial health of companies. Research Method. Correlational research with descriptive methods. Research population some of companies based on BUMN in Jakarta. The variable was the financial aspect based on the Decree of the Minister of BUMN No: KEP 100/MBU/2002 for the last four years. Assessment of the health level of financial aspects using eight indicators, namely ROE, ROI, cash ratio, current ratio, collection periods, inventory turnover, TATO, and Total Capital owned to Total Assets. Findings. The assessment of the company's financial health level. Obtaining a healthy title is expected to be able to always improve health his finances. Conclusion. Financial ratios are a tool to assess the performance of company finances, and to assess the performance company is not enough to only use one or just a few ratios, but is a combination of various financial ratios.